Flexural waves in a periodic non-uniform Euler-Bernoulli beam: Analysis for arbitrary contour profiles and applications to wave control. (15th December 2020) - Li, Peng; Biwa, Shiro
Highlights: The flexural wave in a beam with arbitrary contour profiles is solved via the power series expansion method. The convergence and correctness are proved via FEM. A flexural-wave-based low-pass filter for frequency shunting is designed. A rectangular lens for energy focusing is realized. Abstract: The flexural wave in a periodic non-uniform Euler-Bernoulli beam with arbitrarily contoured profiles is studied by utilizing the power series expansion method. The convergence criterion that makes the power series expansion method applicable is also illustrated. The validation is carried out by comparing the theoretical results with that from the finite element analysis when the beam thickness varies in different forms. For a quadratic thickness variation, the first band gap evolution versus the structural parameter is investigated, based on which a flexural-wave-based low-pass filter for frequency shunting and a rectangular lens for energy focusing are designed. It is revealed in the frequency domain analysis that the flexural wave with a lower frequency can propagate further when it travels into the wave filter. The lens designed exhibits a good focusing phenomenon with the focusing size smaller than one wavelength, and has a good performance at a certain finite frequency range. The theoretical method and design scheme can provide effective guidance for the flexural wave control. Graphical abstract: The flexural wave in an Euler-Bernoulli beam with arbitrarily contoured profiles is solved via the power series expansion method, and applied in the design of a low-pass filter for frequency shunting and a lens for wave focusing. Image, graphical abstract